Effect of the fertilization on some quality parameters of winter wheat - Szabó, Éva; Pepó, Péter (Acta Agraria Debreceniensis, 2010)
We studied the different mineral fertilizer rates effect on the baking quality of five different winter wheat genotypes (GK Öthalom, Lupus, KG Széphalom, GK Békés, Mv Mazurka) on chernozom soil in 2008. The bigger fertilizer doses increased the wet gluten content, gluten elasticity and the protein content. The high doses of fertilization has got a moderate effect on the valorigaph value, water absorption, and falling number. The optimum level of the fertilizer doses were the N90-120+PK. The Pearson’s correlation analysis proved strong relationships between the fertilization and gluten content, the quality of the gluten, a valorigraph value, and the protein content. The analysis verified a strong correlation between genotype and falling number, and the protein content. The variety Mv Mazurka has got the best baking quality parameters.